Public understanding of medical cannabis in Poland 7 years after legalization: findings from a cross-sectional study - Silczuk, Andrzej; Jankowski, Mateusz; Mularczyk-Tomczewska, Paulina; Olearczyk, Agata; Baran, Tomasz; Wrześniewska-Wal, Iwona; Lewandowska, Aleksandra; Łoś, Magdalena (Frontiers in Public Health, 2025)
BackgroundMedical cannabis has been legally available in Poland since 2017, yet its integration into routine clinical practice remains limited. This study investigates public attitudes toward medical cannabis, therapeutic awareness, and the perceived readiness of the healthcare system 7 years after legalization.MethodsA cross-sectional survey was conducted in July 2025 using the computer-assisted web interviewing (CAWI) method on a nationally representative sample of 1,113 adults (aged 18–84). The questionnaire assessed opinions on the legalization of medical cannabis, willingness to undergo cannabinoid-based therapy, perceptions of physician and patient knowledge, and support for home cultivation under medical supervision. Multivariable logistic regression was used to identify sociodemographic predictors of key attitudes.ResultsA substantial majority of respondents supported the legalization of medical cannabis (81.1%) and expressed willingness to undergo treatment if medically indicated (84.3%). However, only 4.2% reported having received a recommendation for medical cannabis from a physician. Confidence in physicians’ (29.9%) and patients’ (16.1%) knowledge about medical cannabis was low. Oncological conditions (57.4%) and chronic pain (49.8%) were the most frequently recognized therapeutic indications. Support for home cultivation was associated with prior medical cannabis use, male gender, younger age, and urban residence. Older adults (≥50 years) were more likely to support legalization, whereas those aged 30–39 and individuals with moderate household income were less accepting.ConclusionWhile public support for medical cannabis in Poland is high, its clinical implementation remains limited. Bridging this gap will require comprehensive educational initiatives and evidence-based guidelines to support healthcare professionals and inform patients.